Tristão de Alencar Araripe e a história da província do Ceará: contribuição à história nacional. - Silva, Leandro Maciel (2013)
This work - belonging to the line of research of Teaching of History and Historical Knowledge in the Post Graduation Program in History of the Federal University of Paraíba, within the área of Historic Culture has as objetive perceive the social place of Tristão de Alencar Araripe both from the standpoint of family and political, as historiography. Tristão was a member of one of the main families of Ceará, which is still remembered for the participation of some of its members in the political events in 1817 and 1824. Under this influence, Tristão opened the writing of history of Ceará. His book, History of the Province of Ceará from earliest times to 1850, published in 1867, is the first methodological effort to write the history of Ceará - Colony to Empire. Tristão wrote his story at the very moment that the Brazilian Historical and Geographical Institute (IHGB) proposed the writing of national history of the Empire of Brazil. One of the strategies to perceive the social place of Tristão is to analyze their relationship with the Institute. The influence of IHGB gave different contours in their work. The defense here is that Tristão wanted to contribute to the writing of national history of the Empire of Brazil. The pretense of Tristão was a national story from the stories local, provincial.